Profit-Sharing and Economic Growth: The Indonesian Experience - Ibrahim, Zaini; Fajri, Muhammad (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: The research's originality investigated the causal relationship between profit-sharing schemes (saving and financing) and economic growth.Research Objectives: This study aimed to examine the effect of profit-sharing schemes in Islamic banking on Indonesia’s economic growth, both in the short and long term. Another objective was investigating the causal relationship between profit-sharing schemes and economic growth.Research Methods: This study used two models: the risk-sharing deposit (RSD) and the profit-and-loss-sharing financing (PLS). It used secondary data from the Financial Services Authority of the Republic of Indonesia, Bank Indonesia (BI), and the Central Bureau of Statistics of the Republic of Indonesia. It also used Nonlinear Autoregressive Distributed Lag (NARDL), Error Correction Model (ECM), and Granger Causality methods to analyze quarterly data for the 2009Q1-2022Q4 period.Empirical Results: The results showed that profit-sharing schemes did not have a significant effect on Indonesia's economic growth in the short-term and long-term because the probability figure was more than 10%. This study obtained new findings, showing that the relationship between the RSD instrument and economic growth followed the feedback hypothesis. Implications: The results of this study had implications for Islamic banking efforts to increase efficiency, improve regulations, and reallocate financing.JEL Classification: G21, O47